Temperament, character traits, and alexithymia in patients with panic disorder - Izci, Filiz; Gultekin, Bulent Kadri; Saglam, Ema; Koc, Merve Iris; Zincir, Selma Bozkurt; Atmaca, Murad (Dove Medical Press Ltd, 2014)
Background: The primary aim of the present study was to compare temperament and character traits and levels of alexithymia between patients with panic disorder and healthy controls. Methods: Sixty patients with panic disorder admitted to the psychiatry clinic at Firat University Hospital were enrolled in the study, along with 62 healthy age-matched and sex-matched controls. The Structured Clinical Interview for DSM-IV axis I (SCID-I), Temperament and Character Inventory (TCI), Toronto Alexithymia Scale (TAS-20), and Panic Agoraphobia Scale (PAS) were administered to all subjects. Results: Within the temperament dimension, the mean subscale score for harm avoidance was significantly higher in patients with panic disorder than in controls. With respect to character traits, mean scores for self-directedness and cooperativeness were significantly lower than in healthy controls. Rates of alexithymia were 35% (n=21) and 11.3% (n=7) in patients with panic disorder and healthy controls, respectively. The difficulty identifying feelings subscale score was significantly higher in patients with panic disorder (P=0.03). A moderate positive correlation was identified between PAS and TAS scores (r=0.447, P < 0.01). Moderately significant positive correlations were also noted for PAS and TCI subscale scores and scores for novelty seeking, harm avoidance, and self-transcendence. Conclusion: In our study sample, patients with panic disorder and healthy controls differed in TCI parameters and rate of alexithymia. Larger prospective studies are required to assess for causal associations.
Keywords: panic disorder; temperament; character; personality; alexithymia